Association between hearing loss, tinnitus, and chronic kidney disease: the NHANES 2015–2018 - Zou, Yihong; Tang, Xiaona; Rao, Kelang; Zhong, Yanghong; Chen, Xushan; Liang, Yuyan; Pi, Ying (Frontiers in Medicine, 2024)
Background Previous studies suggested that chronic kidney disease (CKD) might contribute to hearing loss and tinnitus. Patients with CKD are often at risk of sudden onset hearing loss and tinnitus; however, few epidemiological investigations have been conducted on this topic. The purpose of this investigation was to analyze the correlation between hearing loss, tinnitus, and CKD based on information obtained from the National Health and Nutrition Examination Survey (NHANES). Methods Using data from the NHANES 2015–2018, a cross-sectional analysis was conducted, which included 5,131 participants, and used multivariate logistic regression analyses and subgroup analysis to investigate the association between hearing loss, tinnitus, and CKD. Results CKD was associated independently with hearing loss, with the CKD group being more at risk of hearing loss than the non-CKD group [age-adjusted 95% confidence interval (CI): 1.54 (1.31–1.8), p < 0.001]; multivariable-adjusted 95% CI: 1.31 (1.1–1.55), p = 0.002. Multifactorial logistic regression analysis did not find an association between CKD and tinnitus, however, further subgroup analyses showed a relationship in some populations. Conclusion The results suggested that CKD is associated with hearing loss and tinnitus. The complexity of the relationship between CKD and hearing loss requires further research.